Column absorption and regeneration behavior of a granular red mud for treating wastewater containing methylene blue. Issue 2 (8th January 2016) - Le, T.Q. Xuan; Wang, Hanrui; Ju, Shaohua; Peng, Jinhui; Zhou, Liexing; Dai, Linqing
Abstract: This work focuses on the column absorption and regeneration behavior of a granular red mud (GRM) for absorbing methylene blue (MB) in wastewater. By investigating key parameters, such as packing column height of adsorbent, initial concentration of MB, and flow rate, on the adsorption effects of GRM, the results show that the GRM can effectively remove MB from wastewater. The breakthrough time of the absorption process can be as high as 330 min, when 20.5 cm GRM column was used, with initial concentration and flow rate of MB wastewater being 150 mg L −1 and 4 mL min −1, respectively. The Thomas model is capable of describing the adsorption kinetics. Finally, for assessing the regeneration ability of the loaded GRM, a series of experiments of eluting the MB-loaded column with dilute nitric acid solution, whose pH value is about 3.0, were conducted. The results showed that the regeneration and re-adsorption effect of the GRM column is good.